Teaching Critical Thinking Through Journals Writing in Literature Classes The Case of Third Year Students at the Department of English University of Laghouat - Miloudi, Afaf; Touati ,Nour el Houda; BOUMEDIENE, Houda (University of Ammar Theledji -Laghouat, 2020)
The aim of this research is to teach critical thinking using journals writing. We adopted a hypothesis that supports the idea of writing journals as a way to improve students' reflective writing quality .To achieve the objective of this study, a descriptive-qualitative method was adopted based on a questionnaire and a semi structured interview to collect data. The sample consists of twenty students enrolled at third year English language literature Class. Besides ten teachers at the same department, University of Laghouat.This study took place during the first semester of the academic year 2019/2020. Positive results were found concerning developing students' critical thinking skills through writing mainly journals writing. Most importantly, writing reflective journals proved to be an effective method that will be, successful and enjoyable method. The results of the study revealed that both teachers and students attribute positive comments for integrating journals writing in enhancing critical thinking .Thus, it is recommended to integrate such activity in English Literature Classes